Agroecological evaluation of interrelationships of soil properties in time and space - V. I. Savich; V. V. Gukalov; A. E. Sorokin; M. D. Konakh (Бюллетень Почвенного института им. В.В. Докучаева)
This paper assesses the relationship between the physico-chemical and agro-chemical properties of sod-podzolic soils in the Moscow region and ordinary heavy-loamy chernozems in the Krasnodar region within the catenas and down the soil profile. Soil properties changed significantly through seasonal dynamics. From the end of April to the middle of June in the soil solution of sod-podzolic soils, the value of Eh varied from 534 to 759 mv, the ratio of NO3/NH4 – from 0.2 to 15.4; the content of water-soluble manganese – from 4.0 to 10.1. At the same time, there was a delay in change of soil properties, as humidity and temperature varied. It is shown that in different intervals of soil properties between individual indicators of fertility, the effects of synergism and antagonism are manifested. The degree of mutual influence of soil properties depended on both the degree of soil fertilization and the degree of their cultivation. Information relationships were manifested not only between the soil properties, but also between the processes. Temporary excessive moistening of the soil led to acidification of the soil in the washing type of water mode, and to alkalinization in the non-washing type. It is proposed to account for the relationship of soil properties with humidity, temperature, pH, and Eh to adjust the components of farming systems.